Occurrence of Microplastic Ingestion by Commercial Fish Species from the Pangempang Estuary in Indonesia - Hamdhani, Hamdhani; Ghitarina, Ghitarina; Eryati, Ristiana; Eppehimer, Drew Elliot (Trends in Sciences, 2024)
The aim of this study was to assess the occurrence of microplastic in digestive organs (esophagus to intestine) of popular marine commercial fish species: Jack (Caranx SP.), blackspot snapper (Lutjanus fulviflamma), coral grouper (Epinephelus carallicala), golden snapper (Lutjanus johnii) and pickhandle barracuda (Sphyraena jello) from Pangempang Estuary in Indonesia. To separate the microplastic particles, each sample was digested using alkaline digestion solution, filtered on Whatman paper and then dried. Microplastic particles in the processed digestive organ contents were identified and enumerated using a dissecting stereo microscope. Microplastics were observed in 94 % of fish digestive organs sampled: 100 % jacks (n = 10), 80 % blackspot snapper (n = 10), 100 % coral grouper (n = 10), 90 % golden snapper (n = 10) and 100 % pickhandle barracuda (n = 10). In these fish samples we found in average of 41 ± 6.0, 26 ± 11.0, 15 ± 2.0, 11 ± 1.0 and 14 ± 2.0 SE microplastic particles per individual and an average of 499.5 ± 94.4, 501.5 ± 198.8, 83.6 ± 18.4, 79.8 ± 11.6 and 40.2 ± 25.0 SE microplastic particles per kg fish weight, in jacks, blackspot snapper, coral grouper, golden snapper and pickhandle barracuda, respectively. Fiber was the most dominant type accounting for 78.6 % of all observed microplastics. Microplastic beads were not detected. The correlation of the average consumed microplastic and the average fish weight per species showed a negative relationship (R2 = 0.36), but was not significant (p-value = 0.28). Our finding suggests that demersal fish like jacks, blackspot snapper and coral grouper may have ingested a higher quantity of microplastic particles compared to pelagic species like pickhandle barracuda. HIGHLIGHTS This study demonstrates the presence of microplastic particles in 5 commercially important fish in a tropical estuary of Kalimantan Island in Indonesia Fiber was the most dominant type of microplastic Demersal fish may have ingested a higher quantity of microplastic particles compared to pelagic species GRAPHICAL ABSTRACT